Sistem Reservasi Berbasis Android dengan Dasbor Analitik - Saputro, Tito Zaki; Fachrie, Muhammad (STMIK Banjarbaru, 2025)
The conventional reservation process at Ema Mom Kids Baby Spa has led to various operational issues, such as scheduling errors and inefficient queues. This research aims to address these challenges through the development of an integrated digital reservation system. This study successfully produced a dual-platform system (a mobile application for the business owner and a web platform for customers) that manages booking, schedule, and service data. Testing using the black-box method demonstrated that all core system functionalities from booking to schedule management performed validly. The system also features a descriptive analytics dashboard that serves as a data-driven decision-making tool for the business owner. The developed system has proven effective in improving operational efficiency, minimizing operational errors, and providing strategic business insights.Keywords: Reservation system; Analytics dashboard; Baby spa; Schedule management; Android AbstrakProses reservasi konvensional di Ema Mom Kids Baby Spa memicu antrean yang tidak efisien dan kesalahan jadwal. Untuk mengatasi masalah itu, sebuah sistem reservasi digital terintegrasi dikembangkan. Penelitian ini berhasil menghasilkan sistem dua platform (aplikasi mobile untuk pemilik usaha dan platform web untuk pelanggan) yang mampu mengelola seluruh fungsionalitas utama. Validasi fungsional menggunakan metode black box testing membuktikan bahwa seluruh fitur inti, dari alur pemesanan hingga pengelolaan jadwal, telah berjalan sesuai harapan. Aplikasi ini juga menyediakan dasbor analitik deskriptif yang berfungsi sebagai alat bantu pengambilan keputusan berbasis data bagi pemilik usaha. Implementasi sistem ini terbukti tidak hanya meningkatkan efisiensi dan meminimalkan galat (error) operasional, tetapi juga menyediakan wawasan bisnis strategis bagi pemilik.